Analisis Penginputan SPT Tahunan Wajip Pajak Orang Pribadi 1770 S Dan 1770 SS - Burhanuddin Burhanuddin; Irwan Irwan (Jurnal Bintang Manajemen, 2024)
The Tax Services, Counseling and Consultation Office (KP2KP) is an agency unit belonging to the Directorate General of Taxes (DJP) which is tasked with regulating tax matters. Tax itself is an obligation owed to the state, the amount of which depends on the individual or agency, which is coercive and is stated in statutory regulations. Where later the taxes paid to the state will be used by the state with the main aim of making people's lives prosperous. When reporting or paying taxes, taxpayers are required to come to the office or agency authorized to process taxation. One of the agencies authorized to process taxation is KP2KP or the Tax Services, Counseling and Consultation Office.